Mapping Positions on Forgiving an Aggressor in Sport - Fruchart, Eric; Rulence-Paques, Patricia (Frontiers in Psychology, 2021)
The objective of the present study was to map amateur athletes’ positions on forgiving an aggressor in sport under various circumstances. One hundred and twenty-eight participants judged forgiveness in 32 scenarios built from combinations of five factors (moral disengagement, intention, consequence, apology, and incentive). Following a cluster analysis, ANOVAs, and chi-squared tests, a three-cluster solution was found: “Mainly Forgive, with Non-Additive Integration”, “Seldom Forgive, with Additive Integration”, and “Sometimes Forgive, with Additive Integration”. The clusters’ composition was related to the members’ sex and type of sport. Cluster 1 contained 19% of the women and 32% of the athletes from collision sports. Cluster 2 contained 72% of the men, 53% of the athletes from non-contact sports, and 43% of the athletes from contact sports. Cluster 3 contained 54% of the women, and 58% of the athletes from collision sports.